2020
DOI: 10.3390/ijerph17155365
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Peers’ Autonomy Support and Exercise Intention for Adolescents: Integrating Social Factors from the Self-Determination Theory and the Theory of Planned Behaviour

Abstract: Based on the theory of planned behaviour and self-determination theory, the objective of the present study was to analyse the relationship between (i) parents’ and peers’ autonomy support, and (ii) exercise intention in adolescents, while also considering the mediating role of attitude, control, subjective norms, and descriptive norms. A total of 428 secondary school students, aged between 13 and 19 years old (Mage = 15.30, SD = 1.15), filled in a questionnaire assessing the variables of interest. The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…A study by Chung et al [ 40 ] on seasonal influenza prevention behaviors showed that perceived autonomy support among staff at a Hong Kong elderly center was positively and significantly associated with autonomous motivation to wear masks and indirectly influenced their intentions to wear masks through mediation of attitudes, subjective norms, and perceived behavioral control. Sicilia et al [ 48 ] who integrated SDT and TPB to study an adolescent population, also showed that perceived autonomy support influences intention to exercise through attitude, subjective norm, and perceived behavioral control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Chung et al [ 40 ] on seasonal influenza prevention behaviors showed that perceived autonomy support among staff at a Hong Kong elderly center was positively and significantly associated with autonomous motivation to wear masks and indirectly influenced their intentions to wear masks through mediation of attitudes, subjective norms, and perceived behavioral control. Sicilia et al [ 48 ] who integrated SDT and TPB to study an adolescent population, also showed that perceived autonomy support influences intention to exercise through attitude, subjective norm, and perceived behavioral control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a sample of seventh graders, Beiswenger and Grolnick (2010) found that autonomy within friendships influenced autonomous motivation for after-school activities. Sicilia, Águila, Posse, and Alcaraz-Ibáñez (2020) revealed that peers' autonomy support led to higher levels of exercise intention in leisure time. These results suggest that peer autonomy support can motivate children.…”
Section: Autonomy-supportive Classroom Climatementioning
confidence: 99%
“…Analyses of the effects of gamification on the motivations and academic performance of university students ( n = 127; experimental group = 62, control group = 65), show that its application in physical education led to an increase in students’ academic performance. The ninth manuscript, by Sicilia et al [ 9 ], analyzed the relationship between parental and peer autonomy support and intention to exercise in adolescents ( n = 428) between 13 and 19 years old, also considering the mediating role of attitude, control, subjective norms, and descriptive norms. The results showed that perceived parental autonomy support was positively and statistically significantly associated with exercise intention.…”
Section: The Studies Includedmentioning
confidence: 99%